Conceptual Theoretical Implications in the Reprocessing of the Term Community for the Community-Social Praxis - Burciaga Jiménez, Susana Aurora (Consorcio de Universidades Mexicanas A.C., 2014)
We reflect on the implications of the concept of community from an exercise of social praxis and specifically from the Social Community Psychology (SCP). We planted a substantial difference between the positivist approach and vision SCP releasing through the same concept, retaking certain aspects across different authors proposals on the elements contained in the same. We analyze its consistency according to what we mean by community social praxis. Also, we wonder about the role of certain entities that may be involved in the work of a genuine praxis. We note the relationship between the position of the community mediators in relation to the ideas that can be built around the concept of community. Finally, we required that from any discipline of social studies, including the SCP, it requires work on the reprocessing of those preconceived certainties to avoid falling into asymmetrical power relations with participants in community projects.